The Immunoreactivity of Uroplakin III in Urothelial Carcinoma of Urinary Bladder and Other Non- Urothelial Carcinoma (Medico Legal Update, 2019)
The aim of present study is evaluate the sensitivity and specificity of uroplakin III marker in the urothelialcancer patients, and to show whether there is association this marker with their clinicopathological parameters.This study is a retrospective (70 cases) of whom diagnosis as urothelial carcinoma of urinary bladder (male41 and female 29 ) with added normal urothelial tissue and breast tissue were taken as control group. 41nonurothelial carcinoma are also involved. All paraffin blocks which diagnosed as urothelial carcinomawere supported the diagnosis by pathologist. The all research materials are applied according to protocolfrom, Bio SB, Inc. Uroplakin III immunoreactivity assessment is depend on staining intensity and thepositive percentage tumor cells. The age group between 64-75 years old reveals highest positive value 18(42.9%). Uroplakin III expressions sensitivity is 44.3% , and it has higher positive percentage in low grade20 (47.6%) in comparison with high grade 11(39.3%) but without significant difference (p = 0.492). Ta-1and T2 Tumor stage show 26 (46.4%) and 5(35.7%) positive uroplakin III staining respectively, with nostatistical association between them (p = 0.47). The all non-urothelial carcinoma show negative result(100% specificity). expression of uroplakin III with mild sensitivity and high specificity, it is regarded asgood marker (even with mild sensitivity) for differentiation between primary urothelial carcinoma fromother urological cancers in same site, and it can be useful for diagnosis of unkown metastatic cancer becauseof high specificity of uroplakin III.